Successful Treatment of Streptococcal Toxic Shock Syndrome with Both Diffuse Peritonitis and Necrotizing Fasciitis - Shuichi Sato; Masahiro Ito; Tsuyoshi Sakai; Anri Kaneta; Fumie Sato (Case Reports in Surgery)
Streptococcal toxic shock syndrome (STSS) is a life-threatening disease caused by infection of beta-hemolytic streptococci. Here, we report an uncommon case of STSS with both diffuse peritonitis and necrotizing fasciitis and summarize previous cases. The patient was diagnosed with STSS due to an infection of the soft tissue of the lower extremity after surgery for diffuse peritonitis. The general condition had rapidly deteriorated with multiple organ dysfunction. Immediate intensive care, including mechanical ventilation, hemodiafiltration, and repeated debridement, is indispensable for a favorable outcome.